Drought mitigation potential of Azospirillum inoculation in Canola (Brassica napus) (Journal of Applied Botany and Food Quality, 2016)
Azospirillum is considered to be a most effective Plant Growth Promoting Rhizobacteria (PGPR), which is responsible for various modifications in plants to cope with stress conditions. Therefore, the present research was planned to evaluate the effect of Azospirillum lipoferum (GQ 255949) inoculation on growth, biochemical, yield attributes of canola grown under drought conditions. Two different modes of inoculation were used; i.e., inoculation of seeds directly and exposure of planted seed in the rhizosphere. Drought stress was imposed at flowering stage. Azospirillum seed inoculation was helped mitigate stress effects by improving germination percentage up to 12.49%. Root area was increased up to 18.5% and 11.38% with seed and rhizosphere inoculation in drought stress respectively. Chlorophyll contents and water potential were increased 12.21%, and 11.0% in seeds inoculated under drought conditions. Superoxide dismutase activity was decrease up to 24.6% and 12.5% in seed and rhizosphere inoculated plants under well watered conditions. Seed inoculation was most effective, as number of seeds per pod and seed weight per plant was significantly increased up to 25%, and 14.28% as compared to the control. In conclusion, Azospirillum can mitigate deleterious effects of drought stress in canola under water deficiency conditions.